Sape : The Community Binder - Yakup, bin Mohd Rafee (Pustaka Negeri Sarawak, 2018)
This book is written to provide an account of the substantial contribution of various organisations in bringing forth, and enhancing the level of, traditional sape music – for both national and international audiences. The sape is the traditional musical instrument of the Orang Ulu community, a group of indigenous natives who reside in the Baram area of Sarawak, Malaysia. This tribal group, mainly the Kayan and Kenyah are well known as excellent sape players and good sape makers. Lately, the sape has received tremendous and positive acceptance from the younger generation of Sarawakians. However, continuous efforts are required to conserve and instill further awareness of the musical tradition among this new generation, in order to ensure its continuity. In response to this concern, a research collaboration was initiated among the Faculty of Applied and Creative Arts, Universiti Malaysia Sarawak (UNIMAS); Pustaka Negeri Sarawak, Miri, the organising committees of the Baram Sape Master and The Tuyang Initiative to document information related to the development and achievement of traditional sape music in Sarawak. The recent history of this indigenous music, as elaborated in this book, began with the endeavour of the Baram Sape Master competition – from its inception to successfully staging four winners internationally to promote its appreciation and expansion. To this end, the four winning players were interviewed and visually recorded in Miri and Long San, Baram. This volume also contains interviews with the sape master, Matthew Ngau Jau, regarding his own efforts to promote awareness of traditional sape music. Through the management of The Tuyang Initiative, Mr Matthew's career has grown, not only in Sarawak, but also on the world stage. This book documents as well the rich history of traditional sape-making through the study of two traditional sape makers in Miri and Long Bemang, Baram. For this project, data have been collected in audio-visual format and presented in a colorful and graphical book; a short video documentary accompanies the text. This book also applies Augmented Reality, a reality technology app that enhances the reader's interactive experience with just using a mobile device as a new approach and is the first of its kind to be applied through this book. It is hoped that, with the publication of this book, the efforts and success story of the sape master players can be shared with the global community and, through such means, public awareness of the beauty and importance of traditional sape music can be raised. Importantly also, it is the hope that this endeavour will contribute to preserving and maintaining the identity and culture of the Orang Ulu peoples in Sarawak.